2014
DOI: 10.1080/03075079.2013.858683
|View full text |Cite
|
Sign up to set email alerts
|

Students' preferences in undergraduate mathematics assessment

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 28 publications
2
31
1
Order By: Relevance
“…Moreover, students appear to share this sense of the particular nature of their subject: Iannone and Simpson (2014) found that, contrary to the findings from more generalist literature, the mathematics students in their sample tended to prefer to be assessed by traditional methods and perceived them as better at discriminating between students on the grounds of ability.…”
Section: Introductioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Moreover, students appear to share this sense of the particular nature of their subject: Iannone and Simpson (2014) found that, contrary to the findings from more generalist literature, the mathematics students in their sample tended to prefer to be assessed by traditional methods and perceived them as better at discriminating between students on the grounds of ability.…”
Section: Introductioncontrasting
confidence: 49%
“…Joughin (2010) noted that some key influences on higher education policy and practice may have been over-generalized and that research involving students in particular countries, universities and disciplines may not easily generalize to other contexts. For example, Iannone and Simpson (2014) noted that the vast majority of participants in studies on students' assessment preferences came from just five subject areas (psychology, biology, economics, education and engineering) with none apparently coming from what Biglan (1973) called the 'hard, pure' sciences. Norton, Norton and Shannon (2013) noted that little work has focused on the effect of discipline on assessment practices, though Yorke (2011) argued for a need for a better understanding of the mix of assessment practices in different disciplines and its impact on grades and degree classifications.…”
Section: Introductionmentioning
confidence: 99%
“…The first phase mirrored the approach taken in studies on students' perceptions of assessment (such as Dochy, 2006 andSimpson, 2014) in using an adapted form of the Assessment Preferences Inventory (API) developed by Birenbaum (1994). The API asks participants to rate different forms of assessment according to the study's focus.…”
Section: Methodsmentioning
confidence: 99%
“…The API asks participants to rate different forms of assessment according to the study's focus. The adapted API was based on eight different assessment methods which might be used or applicable to mathematics and which were adopted directly from Iannone and Simpson (2014). These were given with a short description, thus:…”
Section: Methodsmentioning
confidence: 99%
“…They found that students' perceptions differ significantly from what is reported by the general educational literature. Indeed these students prefer to be assessed by assessment methods they perceive to be good discriminators of ability and see the closed book examination as one of the best of these discriminators (Iannone and Simpson 2015a). They also see oral examinations as a very good way to assess for ability in mathematics.…”
Section: How Students Use Online Resourcesmentioning
confidence: 99%